Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5505/kpd.2018.73644
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in sexual functions during and after pregnancy: Prejudice? Or Real?

Abstract: Sexual function in women is a complex and dynamic interaction of multiple variables including physical, emotinal, social, and physiological states. Moreover, sexual function is a key part of each human being's personality and a cornerstone in the overall couple relationship with an obvious affect on health related quality of life. A dysfunction in female sexual cycle can result in lack of desire for sexual contact, arousal and an inability to have an orgasm. Pregnancy is a period with many alterations in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although it is stated in the literature that myths about sexuality cause sexual dysfunction [16] , no studies showing the effects of sexual attitudes on sexual dysfunction during pregnancy have been found. However, some studies in the literature have shown that sexual activity during pregnancy is taboo and avoided in some cultures [17] . While motherhood is accepted as a symbol of purity in different cultures and communities, sexuality is mostly associated with pleasures involving the body, sin, and guilt [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is stated in the literature that myths about sexuality cause sexual dysfunction [16] , no studies showing the effects of sexual attitudes on sexual dysfunction during pregnancy have been found. However, some studies in the literature have shown that sexual activity during pregnancy is taboo and avoided in some cultures [17] . While motherhood is accepted as a symbol of purity in different cultures and communities, sexuality is mostly associated with pleasures involving the body, sin, and guilt [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as sleeplessness, fatigue, lack of time for sexual intercourse, and interventional deliveries may affect sexual life. 22…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was found that increasing age and self‐esteem led to enhanced sexual quality of life and increasing parity impaired sexual quality of life. Factors such as sleeplessness, fatigue, lack of time for sexual intercourse, and interventional deliveries may affect sexual life 22 …”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons why women are afraid and anxious about resuming sexual intercourse after childbirth is the fear of pregnancy. The fact that the woman does not feel sexually aroused during this period and the anxiety and fear of becoming pregnant again have a negative effect on women's sexual life (Beyazıt et al, 2018;Koç & Oskay, 2016;Olsson et al, 2005;Üstgörül, 2016). First sexual intercourse after birth is an important issue for couples (Amir Aliakbari et al, 2018).…”
Section: Contraceptive Usementioning
confidence: 99%